CAUSAL FACTORS INFLUENCING THE EFFICIENCY OF CONDOMINIUM JURISTIC PERSON MANAGEMENT IN THE BANGKOK METROPOLITAN REGION - Boottree, Piyapong; Sirivisitkul, Sanit; Thamchalai, Anan; Kawmongkon, Songyos (Journal of MCU Nakhondhat, 2026)
This research article aims to 1) To examine the influence of the causal relationship model on the management efficiency of condominium juristic persons in the Bangkok Metropolitan Region. and 2) To validate the goodness-of-fit of the model with empirical data. This study employed a quantitative research design. The target population consisted of 2,579 presidents of condominium juristic persons in the Bangkok Metropolitan Region. The data collection instrument was a 5-point Likert scale questionnaire administered to a sample size of 440 respondents, selected through multi-stage and stratified random sampling techniques. Sample size determination was based on the criteria for Structural Equation Modeling (SEM) analysis, which requires a sample size of at least 10 to 20 times the number of observed variables. Given that this study comprised 22 observed variables, a sample size of 440 participants was determined to be appropriate. Statistical data analysis was conducted using Structural Equation Modeling. The developed causal model is consistent with the empirical data. Namely: ( 2 = 190.74, p-value = .120, 2/df = 169, RMSEA < .0017, RMR = .019, GFI = .96, AGFI = .94, NNFI = 1.00, CFI = 1.00) Furthermore, the findings indicated that the causal factors influencing management efficiency with overall means and standard deviations at a high level comprised five key variables: Organizational Climate ( = 3.99, S.D. = 0.34), Organizational Culture ( = 3.97, S.D. = 0.34), Motivation ( = 3.99, S.D. = 0.34), Transformational Leadership ( = 3.99, S.D. = 0.34), and Management Efficiency ( = 3.98, S.D. = 0.34) These results reflect that sustainably enhancing the management efficiency of condominium juristic persons cannot rely solely on developing individual-level factors, such as leadership or motivation, in isolation. Rather, it necessitates an integrated management approach that systematically harmonizes the driving of individual-level factors alongside the development of organizational-level factors.